The Role of Feedback in Learning Differentiated Learning to Support Read-Write Literacy Learners in Elementary School - Intan Budi Komara; Rina Heryani; Mubarok Somantri; Faisal Sadam Murron (Universitas Pendidikan Ganesha, 2025)
The low literacy skills of elementary school students in Indonesia, as indicated by national and international assessments, remain a persistent challenge in the education system. This study aims to analyze the role of feedback in differentiated learning to support and enhance students' reading and writing literacy. A descriptive qualitative approach was used, involving observation, interviews, and document review with purposively selected grade 6 students and a teacher from an elementary school implementing differentiated learning. The research found that the implementation of feedback, both oral and written, significantly improved students' engagement, comprehension, and confidence in literacy learning. Teachers used formative assessments to identify individual difficulties and tailor instructional strategies accordingly. The use of digital tools, such as Google Docs and Quizizz, facilitated timely, interactive, and accessible feedback, enabling students to revise their work more effectively and independently. Students expressed comfort and enthusiasm when receiving feedback that aligned with their learning preferences, whether visual, auditory, or textual. The findings also indicated that feedback strategies supported metacognitive development and fostered learner autonomy in the writing process. In conclusion, this study confirms that the integration of feedback, formative assessment, and technology within a differentiated learning framework can effectively strengthen elementary students’ literacy skills and engagement in the learning process.